2022
DOI: 10.18203/2349-3933.ijam20222096
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio, platelet to lymphocyte ratio and one year survival of lung cancer in Sanglah hospital

Abstract: Background: Lung cancer is ranked third as the most common cancer in Indonesia. The one-year survival rate of advanced-stage non-small cell lung carcinoma (NSCLC) patient is quite low, that is 24.6%. Effective and inexpensive prognostic markers need to be further studied due to an increasing incidence of cancer. Inflammation plays an important role in tumorigenesis and research showed an association of NLR and PLR values with poor prognosis in patients with various solid tumors, but current cut off values stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…Based on the level of education, the study subjects were dominated by a group of patients who never went to school or received primary to secondary education with a case percentage of 86.4%. This finding is in line with the results of a previous study which found that only 9.4% of lung cancer patients received higher education [19] Another study found that 30.8% of lung cancer patients had higher education (Alam, et al, 2020).…”
Section: International Journal Of Scientific Advances Issn: 2708-7972supporting
confidence: 92%
See 3 more Smart Citations
“…Based on the level of education, the study subjects were dominated by a group of patients who never went to school or received primary to secondary education with a case percentage of 86.4%. This finding is in line with the results of a previous study which found that only 9.4% of lung cancer patients received higher education [19] Another study found that 30.8% of lung cancer patients had higher education (Alam, et al, 2020).…”
Section: International Journal Of Scientific Advances Issn: 2708-7972supporting
confidence: 92%
“…In this study, it was found that most of the subjects were working or had worked as much as 82.7% and the rest had never worked or were housewives. This result resembles the findings of a previous study where only 28% were housewives and the rest worked either as farmers, construction laborers, private workers or government workers [19].…”
Section: International Journal Of Scientific Advances Issn: 2708-7972supporting
confidence: 89%
See 2 more Smart Citations